Neuronal excitatory amino acid transporter EAAT3: Emerging functions in health and disease. (February 2019) - Underhill, Suzanne M.; Ingram, Susan L.; Ahmari, Susanne E.; Veenstra-VanderWeele, Jeremy; Amara, Susan G.
Highlights: The glutamate transporter, EAAT3, is implicated in several neuropathological and neuropsychiatric conditions. Modulation of EAAT3 activity may occur through mutations, cellular signaling pathways and alterations in trafficking. EAAT3 knockout mice have deficits in learning, memory and anxiety, especially with age. Further development of tools to modulate EAAT3 are critical to fully understand the impact of EAAT3 on neuronal function.